Upaya Pemerintah Indonesia dalam Menangani Kejahatan Narkotika Sebagai Kejahatan Transnasional - Vanessa Mathilde Harum; Nurul Syarifah (Universitas Batanghari Jambi, 2023)
Drug trafficking is growing rapidly and becoming more sophisticated. It has been organized as a transnational crime which is a form of crime across countries. The drug business has transcended cultural and social boundaries and has become a business that knows no boundaries. This has become a serious problem for every country. This is because this case has caused health problems and crime. Indonesia has become a destination country for drug trafficking. The development of this business has also grown once in the country of Indonesia. Indonesia's vast territory and lack of supervision in border areas make it easy to smuggle these illegal goods. That way, the illicit business can continue. Drug abuse can harm people who use it even to the people around them. Therefore, Indonesia has made efforts in dealing with this transnational drug crime. Therefore, the purpose of this journal is to find out the efforts of the government in Indonesia in dealing with this transnational crime.